Tissue‐specific and time‐dependent clonal expansion of ENU‐induced mutant cells in gpt delta mice. (16th September 2017) - Nakayama, Takafumi; Sawai, Tomoko; Masuda, Ikuko; Kaneko, Shinya; Yamauchi, Kazumi; Blyth, Benjamin J.; Shimada, Yoshiya; Tachibana, Akira; Kakinuma, Shizuko
Abstract : DNA mutations play a crucial role in the origins of cancer, and the clonal expansion of mutant cells is one of the fundamental steps in multistage carcinogenesis. In this study, we correlated tumor incidence in B6C3F1 mice during the period after exposure to N ‐ ethyl‐ N ‐nitrosourea (ENU) with the persistence of ENU‐induced mutant clones in transgenic gpt delta B6C3F1 mice. The induced gpt mutations afforded no selective advantage in the mouse cells and could be distinguished by a mutational spectrum that is characteristic of ENU treatment. The gpt mutations were passengers of the mutant cell of origin and its daughter cells and thus could be used as neutral markers of clones that arose and persisted in the tissues. Female B6C3F1 mice exposed for 1 month to 200 ppm ENU in the drinking water developed early thymic lymphomas and late liver and lung tumors. To assay gpt mutations, we sampled the thymus, liver, lung, and small intestine of female gpt delta mice at 3 days, 4 weeks, and 8 weeks after the end of ENU exposure. Our results reveal that, in all four tissues, the ENU‐induced gpt mutations persisted for weeks after the end of mutagen exposure. Clonal expansion of mutant cells was observed in the thymus and small intestine, with the thymus showing larger clone sizes. These results indicate that the clearance of mutant cells and the potential for clonal expansion during normal tissue growth depends on tissue type and that these factors may affect the sensitivity of different tissues to carcinogenesis. Environ. Mol. Mutagen. 58:592–606, 2017. © 2017 Wiley Periodicals, Inc.